A new formulation for estimating maximum stress intensity factor at the mid plane of a SENB specimen: Study based on 3D FEA (Fracture and Structural Integrity, 2014)
In this investigation, three-dimensional elastic finite element analyses have been conducted to compute the stress intensity factor (KI) in a SENB specimen with varied thickness (B) and crack-length to width ratio (a/W). The results indicate that the magnitude of KI depends on B, and significantly varies along the crackfront from surface to the center of the specimen. The maximum value of KI is found at mid plane of the specimen. Based on the present 3D finite element calculations an effort is made to propose the new analytical relationship between maximum KI and specimen a/W, which helps to estimate maximum KI by only knowing specimen geometry and applied load.
Keywords: Maximum stress intensity factor